A fantasia como realidade do sujeito: uma leitura psicanalítica a partir do trabalho do psicólogo com crianças em situação de violência sexual - RODRIGUES, Simone de Miranda (2016)
Starting from the psychologist's work with children in situations of sexual violence in the legal context we had asked in our practice, electing as theoretical referential the psychoanalytic theory. Thus, the implications are discusses in the work of the professionals who treat cases involving sexual matters between persons of the same family background, of different generations, driven by the search for the guilty to be punished. A discussion with the expansion of sexuality notion proposed by Freud admits that infantile sexuality and shows that sex is structural and always traumatic it is open. Interlace this discussion with the unconscious notion of inaugural concept of psychoanalysis, marking the Freudian and Lacanian reading way to situate the unconscious structured as a language, supported the theory of the signifiers. It is shown that to pay attention to empirical data, some concepts are correlated, such as sexuality, fantasy and Oedipus-Castration Complex. Then deals with the constitution of the subject from the proposal made by Lacan's mirror where the stadium is evident precipitation as taking position in the social. It presents the hypothesis of the primacy of the phallus as sexuality organizer which has at its center the articulated desire to castration, where is evidenced fantasy as reality of the subject, considering versions of his father in ultimately the enacting of Law, to that depriving the mother of reintegrating their product. Terminate the discussion resuming the initial question of the subject's relation to sexuality and the law, opening new questions that allows a shift of the practice, which permeated by impasses and supports, enables the speech of a child in situations of violence sex is considered beyond the legal rite, a so-called reality of the subject